2012
DOI: 10.1007/s10120-011-0122-5
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine carcinoma of the stomach: clinicopathological analysis of 27 surgically treated cases in a single institute

Abstract: Background Gastric endocrine carcinoma (EC) is an uncommon tumor of the stomach and the clinical features are not well known. Additionally, the classification and staging systems of this tumor are not yet unified worldwide. In this study, we reviewed 27 patients with gastric EC to evaluate the clinicopathological characteristics of this tumor. Methods We retrospectively reviewed 27 patients with gastric EC among 6466 patients who had undergone gastrectomy between 1986 and 2008 at our institute. Clinicopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 21 publications
6
46
1
Order By: Relevance
“…Our results showed that a higher Ki-67 PI was associated with more advanced disease such as larger tumor size, deeper tumor invasion, and lymph node or distant metastasis in gastric WDNET, which is consistent with previous studies [10][11][12]. Prognostic value of WHO 2010 grading system based on Ki-67 PI has been validated in GI neuroendocrine neoplasms by others [6,7].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that a higher Ki-67 PI was associated with more advanced disease such as larger tumor size, deeper tumor invasion, and lymph node or distant metastasis in gastric WDNET, which is consistent with previous studies [10][11][12]. Prognostic value of WHO 2010 grading system based on Ki-67 PI has been validated in GI neuroendocrine neoplasms by others [6,7].…”
Section: Discussionsupporting
confidence: 93%
“…However, Ki-67 PI in the clinical subtypes of gastric WDNET has not been evaluated in detail. Also, only a few studies have reported correlation between Ki-67 PI and clinicopathologic factors of gastric WDNET [10][11][12]. We aimed to evaluate clinicopathologic characteristics and Ki-67 PI status in the clinical subtypes of gastric WDNET in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Although NEC is categorized as a neuroendocrine neoplasm, it is clearly differentiated from other neuroendocrine tumors by its highly malignant biological behavior (24). In addition, gastric NEC is considered to have a poorer prognosis than gastric adenocarcinoma (GAD), with a high incidence of metastasis to the lymph nodes or liver in the early stages of the disease (12,16). However, as gastric NEC is morphologically similar to poorly differentiated adenocarcinoma with a predominantly solid growth pattern (12), it is difficult to distinguish using hematoxylin and eosin staining only.…”
mentioning
confidence: 99%
“…Early diagnosis is an important factor for avoiding extensive resection like in the case reported in this study. 14 The prognosis for patients with MANECs is not well-defined. 15,16 The data available suggest that high grade MANECs appear to lead to better overall survival than do pure neuroendocrine carcinomas.…”
Section: Discussionmentioning
confidence: 99%